The Role of the von Willebrand Factor Collagen-Binding Assay (VWF:CB) in the Diagnosis and Treatment of von Willebrand Disease (VWD) and Way Beyond: A Comprehensive 36-Year History - Favaloro, Emmanuel J. (Seminars in Thrombosis and Hemostasis, 2023)
The von Willebrand factor (VWF) collagen binding (VWF:CB) assay was first reported for use in von Willebrand diagnostics in 1986, by Brown and Bosak. Since then, the VWF:CB has continued to be used to help diagnose von Willebrand disease (VWD) (correctly) and also to help assign the correct subtype, as well as to assist in the monitoring of VWD therapy, especially desmopressin (DDAVP). However, it is important to recognize that the specific value of any VWF:CB is predicated on the use of an optimized VWF:CB, and that not all VWF:CB assays are so optimized. There are some good commercial assays available, but there are also some “not-so-good” commercial assays available, and these may continue to give the VWF:CB “a bad reputation.” In addition to VWD diagnosis and management, the VWF:CB found purpose in a variety of other applications, from assessing ADAMTS13 activity, to investigation into acquired von Willebrand syndrome (especially as associated with use of mechanical circulatory support or cardiac assist devices), to assessment of VWF activity in disease states in where an excess of high-molecular-weight VWF may accumulate, and lead to increased (micro)thrombosis risk (e.g., coronavirus disease 2019, thrombotic thrombocytopenic purpura). The VWF:CB turns 37 in 2023. This review is a celebration of the utility of the VWF:CB over this nearly 40-year history.
Keywords: von Willebrand factor; von Willebrand disease; VWF:CB; VWF:RCo; VWF:GPIbR; VWF:GPIbM; VWF:Ag; diagnosis; management; history